1993
DOI: 10.1007/bf01886222
|View full text |Cite
|
Sign up to set email alerts
|

Food potentials of some unconventional oilseeds grown in Nigeria — A brief review

Abstract: A brief review of literature on kernels of Citrullus and Cucumeropsis ('egusi' melon) species, Telfairia occidentalis (fluted pumpkin), Lagenaria (gourd) species of all of Cucurbitaceae family and other oilseeds such as Pentaclethra macrophylla (African oil bean), Parkia spp. (African locust bean) both of Mimosaceae family and Butyrospermum paradoxum (shea butter) of Sapotaceae family which are grown and widely used as food in Nigeria is presented. The kernels of species of Cucurbitaceae form the bulk of uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 19 publications
0
32
0
2
Order By: Relevance
“…The indigenous edible-seeded cucurbits are classified into the minor crops. There are several species of cucurbit in tropical Africa and Asia, cultivated mainly for their oleaginous seeds that are important in the social and cultural life of several peoples (Badifu, 1993;Das et al, 2002;Enujiugha and Ayodele-Oni, 2003;Achu et al, 2005;Zoro Bi et al, 2005). Cucumeropsis mannii Naudin belonging to this category of crop, is one of the most widely distributed and consumed at both rural and urban levels in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indigenous edible-seeded cucurbits are classified into the minor crops. There are several species of cucurbit in tropical Africa and Asia, cultivated mainly for their oleaginous seeds that are important in the social and cultural life of several peoples (Badifu, 1993;Das et al, 2002;Enujiugha and Ayodele-Oni, 2003;Achu et al, 2005;Zoro Bi et al, 2005). Cucumeropsis mannii Naudin belonging to this category of crop, is one of the most widely distributed and consumed at both rural and urban levels in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In Sub-Saharan Africa, C. mannii is prized for its oleaginous seeds consumed as thickeners of a traditional soup called egussi soup in Cameroon, Nigeria or Benin and pistachio soup in Côte d'Ivoire (Enujiugha and Ayodele-Oni, 2003;Achu et al, 2005;Zoro Bi et al, 2005;Loukou et al, 2007). This cucurbit is reported to be rich in nutrients (Badifu, 1993;Enujiugha and Ayodele-Oni, 2003;Achu et al, 2005), namely protein (36 AE 2.17%) and fat (45.89 AE 4.73%). In addition, commonly found in many traditional cropping systems, the plant is well adapted to extremely divergent agroecosystems and various cropping systems characterised by minimal inputs (Achu et al, 2005;Achigan Dako et al, 2006;Zoro Bi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Les huiles non conventionnelles constituent une alternative de développement pour les populations des pays émergents [1]. Parmi elles, les graines de cucurbitacées avec leur forte teneur en lipides sont de bonnes candidates [2,3].…”
Section: Introductionunclassified
“…It is a deep rooted drought resistance perennial shrub grown throughout the world under different climatic and cultural conditions [17,18]. In Nigeria, the plant has been listed as one of the underutilized legumes with broad potentials [19][20][21][22]. Several clinical studies have revealed the potential use of pigeon pea seed as melanin based in the dietary management of diabetes mellitus and cardiovascular diseases [23].…”
Section: Common Legume Foods Grown In Nigeriamentioning
confidence: 99%